The Implementation of Project-Based Learning in Developing 21st Century Skills in EFL Class - Sah, Firman; Naura Sasikirana , Herlya; Pujiani, Tri (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
The usefulness of Project-Based Learning (PBL) in fostering the development of critical thinking, teamwork, communication, creativity, and digital literacy—all crucial 21st-century skills—is examined in this paper. Based on constructivist learning theories, such as those proposed by Lev Vygotsky and John Dewey, the study emphasizes PBL as a student-centered method that encourages experiential learning via practical projects. Through active problem-solving and teamwork, these projects help students grow in their ability to think critically and creatively. A narrative literature review was used as part of the study's approach to compile pertinent studies related to Project-based learning. The conceptual framework for the analysis concentrated on the ways in which PBL develops essential competencies, paying special emphasis to student participation, technological integration, and collaborative learning. The results show that by challenging students to apply their knowledge to solve real-world situations, PBL dramatically improves critical thinking. Additionally, it fosters creativity by supporting invention and concept experimenting. Teamwork in PBL environments fosters collaboration, an essential ability in today's businesses. PBL also helps students become better communicators since they have to explain their thoughts and provide solutions. PBL's incorporation of digital technologies improves digital literacy even further and gets pupils ready for a world where technology is everywhere. To sum up, PBL is an effective teaching strategy for cultivating 21st-century competencies. However, sufficient training for teachers, institutional backing, and fair access to digital resources are necessary for successful implementation. PBL is recommended for use by educators in order to help students become lifelong learners and better equipped for the complexity of the modern workforce.